A highly diastereoselective [5+1] annulation to 2, 2, 3-trisubstituted tetrahydroquinoxalines via intramolecular Mannich-type trapping of ammonium ylides12. Issue 66 (30th July 2019) - Guan, Xiao-Yu; Tang, Min; Liu, Zhang-Qin; Hu, WenHao
Abstract : A highly diastereoselective [5+1] annulation to 2, 2, 3-trisubstituted tetrahydroquinoxalines was developed by us. Abstract : A novel tandem intermolecular ammonium ylide formation/intramolecular Mannich-type [5+1] cyclization reaction of aryl diazoacetates and ortho -aminophenyl imine derivatives was developed. The reaction provides an efficient methodology for direct synthesis of diverse trisubstituted tetrahydroquinoxalines bearing a quaternary stereogenic carbon center in moderate to good yields with excellent diastereoselectivity. This process features high efficiency, mild reaction conditions, and high stereoselectivity.